WANDERING SPLEEN WITH TORSION AND RESULTANT INFRACTION - Nishtar, Tahira; Amin, Ayesha (Journal of Postgraduate Medical Institute, 2011)
We present a case report of a 40 -year-old woman presenting with left loin pain and a palpable suprapubic mass and anemia. Ultrasonography and subsequent contrast enhanced CT scan showed that spleen was not seen in its normal anatomical position and a comma shaped spleen was present in pelvis with non-enhancing soft tissue density consistent with infarction. Splenectomy was performed.